The Influence of A Cross‐Reef Channel On the Wave‐Driven Setup and Circulation at Ipan, Guam. Issue 7 (1st July 2020) - Clark, S. Jeanette; Becker, Janet M.; Merrifield, Mark A.; Behrens, James
Abstract: The influence of a deep (30 m), narrow (30 m) cross‐shore channel on the circulation and wave‐induced setup over a shallow (∼0.5 m) and wide (∼400 m) shore‐attached fringing reef is examined using field measurements collected at Ipan, Guam. Mean currents on the reef flat over a 7‐week study period during mid and high tides when the reef is submerged are directed toward the channel with the alongshore component of the current increasing with proximity to the channel. The cross‐shore component of the reef flat current is directed onshore at the sensors in the far‐field of the channel with a weak offshore flow at the current meter located closest to the channel (∼760 m to the north). Low‐frequency fluctuations of the alongshore reef flat current and offshore channel current are significantly correlated and with the incident significant wave height. Mean and low‐frequency fluctuating currents are forced by the spatially variable wave‐driven setup, modulated by tidal elevation, which creates a pressure gradient over the reef flat due to the channel where waves do not break. The dominant alongshore momentum balance on the reef flat is between the pressure gradient and bottom stress, with an inferred drag coefficient of C D  ∼ 0.01. A simple analytical model is presented that is consistent with the observations and delineates the near‐ and far‐field of the channel as a function of the aspect ratio of the reef. Observations from a longer deployment of channel currents are highly correlated with incident wave height in distinct tidal level bands. Plain Language Summary: Observations of waves, water levels, and currents at Ipan, Guam, are analyzed to determine how wave‐driven flow on a shore‐attached fringing reef is influenced by a cross‐reef channel. Breaking waves at the outer reef cause elevated water levels over the reef flat. At the deep, narrow channel wave breaking is suppressed, resulting in a pressure gradient that forces a rip circulation toward and out the channel. The dominant physical balance between bottom friction and this pressure gradient leads to an estimate of a drag coefficient C D  ∼ 0.01. The wave‐driven channel current is modulated by tidal submergence of the reef flat, and the flow scales with offshore wave heights at high tidal levels. A simple analytical model describes the spatially variable pressure gradient and defines the region of influence of the channel as a function of the length to width ratio of the reef flat. Key Points: Breaking wave setup over a shore‐attached fringing reef is suppressed by a deep, narrow channel generating an alongshore pressure gradient A steady rip circulation on the reef flat and out the channel is generated that is highly correlated with wave height and tidal level The balance between bottom drag and the induced pressure gradient leads to an inferred drag coefficient of C D ∼0.01